Neopatrimonialism in the 2020 Regional Head Elections in the Power Cube Perspective - Muhammad Aqiel; Ananda Putri Sujatmiko (Bestuurskunde: Journal of Governmental Studies, 2021)
The number of candidates who have a kinship with political and/or government entities in the 2020 Pilkada in Indonesia has shot up compared to the previous period, namely originally 59 candidates (2005-2014 period), 86 candidates (2015-2018 period), now 124 candidates (2020-2024 period). The research aims to identify the most dominating dimensions of power in kinship politics by using the power cube theory. In summary, the power cube theory analyzes the interaction of power in 3 (three) dimensions, namely levels, spaces, and forms. The method used is a quantitative method with analytical hierarchy process techniques to determine the criteria for the highest kinship politics and to determine the regions with the highest kinship political relations based on the criteria. Researchers identified the potential impact of kinship politics practice using descriptive qualitative research methods. The results of the study found a visible dimension in the power cube theory, namely that poor regeneration of political parties dominates the causes of kinship politics (73% of the criteria weighted results). The regions with the highest kinship politics based on the criteria for weak party regeneration were South Sulawesi (60.3%), followed by Sumatra (24.88%) and Java (10.07%). There are 5 (five) potential impacts of the practice of kinship politics, namely versatile coalitions, policies originating from elite compromise, marginalized crucial public issues, the birth of regulations that accommodate the interests of actors outside of government, and the declining performance of the bureaucracy in bridging the needs of the people.